2004
DOI: 10.1086/423942
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the Interleukin‐10 Promoter Affects Both Provirus Load and the Risk of Human T Lymphotropic Virus Type I–Associated Myelopathy/Tropical Spastic Paraparesis

Abstract: To investigate non-human leukocyte antigen candidate genes that influence the outcome of human T cell lymphotropic virus (HTLV) type I infection, we analyzed 6 single-nucleotide polymorphisms in the interleukin (IL)-10 promoter region in 280 patients with HTLV-I-associated myelopathy/tropical spastic paraparesis (HAM/TSP) and 255 HTLV-I-seropositive asymptomatic carriers from an area where HTLV-I is endemic. The IL-10 -592 A allele, which shows lower HTLV-I Tax-induced transcriptional activity than the C allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 33 publications
2
41
0
Order By: Relevance
“…Conversely, a Caribbean study that examined SNPs in 38 gene candidates found that SNPs in the coding regions of IL13 (A98G) and VCAM1 (G149A)—both of which are known to be upregulated in HTLV-1-infected T cells—were associated with decreased risk for ATL development (161). In HAM/TSP patients, expansions of a CA repeat polymorphism in the MMP9 gene correlate with development of disease (78), and individual SNPs in the immunity-related cytokine genes IL18, IFNG, IL28B, and IL10 have each been associated with higher proviral load (5, 127, 128). Such findings further highlight the genetic complexity underlying HTLV-1-mediated disease.…”
Section: Human T Cell Leukemia Virus Typementioning
confidence: 99%
“…Conversely, a Caribbean study that examined SNPs in 38 gene candidates found that SNPs in the coding regions of IL13 (A98G) and VCAM1 (G149A)—both of which are known to be upregulated in HTLV-1-infected T cells—were associated with decreased risk for ATL development (161). In HAM/TSP patients, expansions of a CA repeat polymorphism in the MMP9 gene correlate with development of disease (78), and individual SNPs in the immunity-related cytokine genes IL18, IFNG, IL28B, and IL10 have each been associated with higher proviral load (5, 127, 128). Such findings further highlight the genetic complexity underlying HTLV-1-mediated disease.…”
Section: Human T Cell Leukemia Virus Typementioning
confidence: 99%
“…In the same cohort, the host genotype was determined (Vine et al, 2002;Kodama et al, 2004;Sabouri et al, 2004) at over 70 single-nucleotide polymorphisms (SNPs) in over 50 loci outside HLA class 1. Of these, polymorphisms at four loci (TNFA, IL-15, SDF-1 and IL-10) had statistically significant independent effects on the proviral load or the risk of HAM/TSP, or both.…”
Section: Htlv-1-specific Ctls Must Be Highly Active In Vivomentioning
confidence: 99%
“…The final published version may differ from this proof. In this context, many studies have demonstrated an association between mutations in human genes, diseases manifestation and viral infections influence [34][35][36] .…”
Section: Resultsmentioning
confidence: 99%